(untitled) (International Journal of Engineering Materials and Manufacture, 2018)
The aim of this research was to evaluate the level of greenhouse gas emission from broiler chicken farming industry in Malaysia. In order to achieve that, Life Cycle Assessment method was chosen as a framework to complete the task. A case study was conducted at a broiler chicken farm to gather the data and information related to the broiler chicken production. Cradle-to-gate assessment including distribution stage was conducted based on the ISO14040/1044 guidelines. Inventory data for this case study was gathered in collaboration with one of the selected case study broiler chicken farm company. Greenhouse gas emission that consists of several most affected gases such as carbon dioxide, methane and nitrous oxide was studied. Result shows that the highest carbon dioxide emission came from manure, which accounted for 1,665,342 kg CO2 equivalent per total broilers while the highest methane emission came from feed, which accounted for 126,207.84 g CH4 equivalent per total broilers. For nitrous oxide emission, the highest values came from bedding which accounted for 20,316.87 g N2O equivalent per total broilers in the commercial modern broiler chicken farm. In this case study, it can be concluded that manure gives the most prominent effect to the greenhouse gas emission followed by feed and bedding materials.